Development of reading comprehension in bilingual and monolingual children—effects of language exposure - Papastefanou, Theodora; Marinis, Theodoros; Powell, Daisy (My University, 2021)
The current study aimed at investigating the performance of bilingual children with English as an additional language (EAL) on language and literacy measures compared to monolinguals across the first four years of primary school in the U.K. Moreover, it addressed whether bilinguals and monolinguals’ performance on reading comprehension was consistent with the Simple View of Reading. An additional area of interest was to examine the extent to which use of and exposure to both heritage and majority language affected the development of the children’s reading comprehension in both of their spoken languages. A total of forty bilingual and forty monolingual children were assessed in oral language skills and decoding in Year 1 and Year 3 in primary school. After one school year, they were assessed in oral language skills, decoding, and reading comprehension in Year 2 and Year 4. The results showed that the bilinguals performed better than the monolinguals in decoding in all years, suggesting that exposure to a first language with transparent orthography (Greek) may benefit the development of word reading skills. However, the bilinguals scored lower in oral language skills and reading comprehension than their monolingual peers. This finding underlined the significant role of oral language skills in the development of bilinguals’ reading comprehension. Both oral language skills and decoding contributed to reading comprehension in bilinguals but the effects of oral language skills on reading comprehension were stronger than the effects of decoding. Finally, we found that language use of the minority language outside the home could significantly predict reading comprehension in the minority language, underlining the importance of language exposure through complementary schools and other activities outside the home to the maintenance and development of the heritage language.
Keywords: Oral language skills; Reading comprehension; Decoding; English as a second language; Language exposure